A ROS-responsive biomimetic nano-platform for enhanced chemo-photodynamic-immunotherapy efficacy. (13th October 2022) - Yan, Huixian; Zhang, Yanan; Zhang, Yu; Li, Yingying; Kong, Xinru; Liu, Dongzhu; Li, Jin; Xi, Yanwei; Ji, Jianbo; Ye, Lei; Zhai, Guangxi
Abstract : Due to the complex bloodstream components, tumor microenvironment and tumor heterogeneity, traditional nanoparticles have a limited effect (low drug delivery efficiency and poor penetration to the deeper tumor) on eradicating tumors. Abstract : Due to the complex bloodstream components, tumor microenvironment and tumor heterogeneity, traditional nanoparticles have a limited effect (low drug delivery efficiency and poor penetration to the deeper tumor) on eradicating tumors. To solve these challenges, novel platelet membrane-coated nanoparticles (PCDD NPs) were constructed for combined chemo-photodynamic- and immunotherapy of melanoma. The platelet membrane imparted the PCDD nanoparticles with an excellent long circulation effect and tumor targeting ability, which solved the issues of low drug delivery efficiency. After reaching the tumor cells, it releases the drug-loaded CDD micelles, becoming positively charged and facilitating the deep penetration of tumors. Cytotoxic and apoptosis experiments showed that PCDD nanoparticles have the strongest tumor cell killing ability. Based on the excellent results in vitro, PCDD was used to assess anti-tumor and distal tumor inhibition in rat models. The results revealed that the PCDD combined PDT, immunotherapy and chemotherapy could not only inhibit the primary tumor growth (inhibition rate: 92.0%) but also suppress the distant tumor growth (inhibition rate: 90.7%) and lung metastasis, which is far more effective compared to the commercial Taxotere®. Exploration of the molecular mechanism showed that in vivo immune response induced an increase in positive immune responders, suppressed negative immune suppressors, and established an inflammatory tumor immune environment, leading to excellent results in tumor suppression and lung metastasis. In conclusion, this novel multifunctional PCDD nanoparticle is a promising platform for tumor combined chemotherapy, photodynamic therapy (PDT) and immunotherapy.